1990
DOI: 10.1021/bi00478a019
|View full text |Cite
|
Sign up to set email alerts
|

Calcium binding in .alpha.-amylases: an x-ray diffraction study at 2.1-.ANG. resolution of two enzymes from Aspergillus

Abstract: X-ray diffraction analysis (at 2.1-A resolution) of an acid alpha-amylase from Aspergillus niger allowed a detailed description of the stereochemistry of the calcium-binding sites. The primary site (which is essential in maintaining proper folding around the active site) contains a tightly bound Ca2+ with an unusually high number of eight ligands (O delta 1 and O delta 2 of Asp175, O delta of Asn121, main-chain carbonyl oxygens of Glu162 and Glu210, and three water molecules). A secondary binding site was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
213
1
5

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(227 citation statements)
references
References 33 publications
8
213
1
5
Order By: Relevance
“…In conclusion, it is suggested that the fifth conserved sequence region (173_LPDLD in TAA) recognised firstly in the sequences of a-amylases [11] and now demonstrated in the sequences of the other known enzymes from this family (Table 1) should be taken into account in studying both structurefunction (Asp-175 in TAA is the calcium ion ligand [12]) and evolutionary relationships (this work) of these enzymes. Although the characteristic sequence differences that allow to discriminate functionally and structurally closely related enzymes, such as a-amylases and cyclodextrin glycosyltransferases, can be revealed (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, it is suggested that the fifth conserved sequence region (173_LPDLD in TAA) recognised firstly in the sequences of a-amylases [11] and now demonstrated in the sequences of the other known enzymes from this family (Table 1) should be taken into account in studying both structurefunction (Asp-175 in TAA is the calcium ion ligand [12]) and evolutionary relationships (this work) of these enzymes. Although the characteristic sequence differences that allow to discriminate functionally and structurally closely related enzymes, such as a-amylases and cyclodextrin glycosyltransferases, can be revealed (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The region contains the Asp-175 (Aspergillus oryzae c~-amylase (TAA) numbering) mostly involved in the binding of Ca 2÷ (e.g. [12]). It is worth mentioning that not only the sequence of this region is conserved.…”
mentioning
confidence: 99%
“…Comparing the intermediate ring puckering parameters with those of small molecule X-ray structures and a potential map from molecular mechanics calculations indicates that the sugar bound to Asp 229 has a low-energy 4 C 1 chair conformation 15 . 20 then attacks the C1 atom of the sugar at subsite -1, the transition state 12 for this first step being stabilized electronically by the negative potential that reigns in the catalytic site 26 , possibly assisted by the partial negative charge of the p-cloud in the aromatic ring of Tyr 100 27 . In addition, the proximity of the carbonyl oxygen of Asp 229 to the glucose ring O5 atom (as observed in the intermediate structure) may ensure a favorable interaction during transition state formation, when Asp 229 bears a partial negative charge, and O5 a partial positive charge.…”
Section: Mechanism Of the First Reaction Stepmentioning
confidence: 99%
“…225, 11-24 (1992 line using an ADSC Quantum4 CCD detector and processed using MOSFLM 25 . Molecular replacements were performed with AMORE 26 , ncs averaging of electron density was performed with DPHASE (G.V., unpublished) and model building was peformed in O 27 . Heavy atom refinement, isomorphous difference phasing, and combination with molecular replacement phases for apoArgRBst were performed in a modified version of MLPHARE 28 .…”
mentioning
confidence: 99%
“…The histogram in Figure 13 (top left) represents the search with the catalytic triad consensus template derived from the Ser 195 07-His 195 side-chain-Asp 102s2 catalytic triad from llpr (Bone et al, 1991). The other three histograms are searches using noncatalytic Ser-His-Asp interactions that have an RMSD between 3 8, and 6 8, from the llpr consensus template; these are Ser 202 OY-His 205 side-chain-Asp 172 Os* from chicken annexin lala (Bewley et al, 1993), Ser 13 OY-His 503 side-chain-Asp 518 Os2 from cyclodextrin glycosyltransferase lcdg (Lawson et al, 1994), and Ser 104 OY-His 108 side-chain-Asp 201 Os' from a-amylase 2aaa (Boel et al, 1990). For the catalytic triad search, 20 other catalytic triads are located from the data set of structurally nonidentical proteins, compared to only one for each of the noncatalytic Ser, His, and Asp interactions.…”
Section: -mentioning
confidence: 99%